PERLINDUNGAN HUKUM SERTA BATASAN HUKUMAN OLEH GURU KEPADA MURID DALAM PELAKSANAAN PENDIDIKAN - Mansur, Moch; Mangar, Irma; Kholifah, Ummu Nur (Universitas Muhammadiyah Ponorogo, 2024)
In a review of recent empirical studies and research to assess whether punishment actually helps create a better learning environment or actually contributes to deeper behavioral problems. The impact of punishment on students psychologically and emotionally. The focus includes the short-term and long-term implications of harsh and inappropriate punishment on students' mental development and psychological well-being. This normative-empirical legal research method is basically a combination of a normative legal approach with the addition of various empirical elements. The government's efforts to protect educators in their work are referred to as legal protection for teachers. This includes protection in the fields of law, welfare, education, and society. In its implementation, punishment must be proportional to the violation or mistake made by the student. Punishment that is too severe or disproportionate to the violation can be considered unfair and can affect students' relationships with school and learning.